2022
DOI: 10.3390/microorganisms10051049
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Elevational Patterns and Their Linkages of Soil Bacteria and Plant Community in An Alpine Meadow of the Qinghai–Tibetan Plateau

Abstract: Soil microbes play important roles in determining plant community composition and terrestrial ecosystem functions, as well as the direction and extent of terrestrial ecosystem feedback to environmental changes. Understanding the distribution patterns of plant and soil microbiota along elevation gradients is necessary to shed light on important ecosystem functions. In this study, soil bacteria along an elevation gradient in an alpine meadow ecosystem of the Qinghai–Tibetan Plateau were investigated using Illumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…The soil contains a diverse range of microorganisms, with bacteria and fungi being the most abundant [4]. Studies have shown that in alpine meadows the bacterial community is mainly composed of Proteobacteria and Acidobacteria, and the most numerous fungal communities are Ascomycota and Basidiomycota, and not only with high plasticity and adaptability to the environment, but also, perform a vital function in crucial processes such as plant production, greenhouse gas emissions, and nutrient cycling, which are essential for the maintenance of numerous ecosystem functions [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The soil contains a diverse range of microorganisms, with bacteria and fungi being the most abundant [4]. Studies have shown that in alpine meadows the bacterial community is mainly composed of Proteobacteria and Acidobacteria, and the most numerous fungal communities are Ascomycota and Basidiomycota, and not only with high plasticity and adaptability to the environment, but also, perform a vital function in crucial processes such as plant production, greenhouse gas emissions, and nutrient cycling, which are essential for the maintenance of numerous ecosystem functions [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%